PERSEPSI KONTROVERSI KEPEMIMPINAN WANITA PADA NEGARA MAYORITAS MUSLIM DI INDONESIA - Helma Winda; Mochamad Aris Yusuf; Hoirul Anam (Institut Agama Islam Negeri Ponorogo, 2023)
Exist the statement that women only have the task of taking care of household affairs, so that with this fact women become marginalized. Even though Islam itself has clarified religion which gives an equal position regarding men and women with matters of worship, for example. So this article wants to delve deeper into the perception of the leadership controversy among women in Indonesia. Achieved through research methods with the type of qualitative research methods based on field research. The results obtained in this study, that the public's perception of women's leadership, there are five things, namely: women's rights but based on consideration, someone who can carry out the mandate, gender equality, through the basis of hadith and also the Koran, and women do not have the ability to become leaders.